A prospective study on patterns of use of schizophrenia medications in outpatient pharmacy department, Hospital Tengku Ampuan Rahimah, Selangor, Malaysia - Ponto, Thellie; Ismail, Nurul Izwani; Abdul Majeed, Abu Bakar; Marmaya, Najihah Hanisah; Zakaria, Zainul Amiruddin (Prous Science, 2010)
Schizophrenia is a chronic psychiatric disorder and pharmacotherapy plays a major role in its management. The 1950s and early 1960s saw milestones in the introduction of psychotropic drugs in clinical practice. A review of drug prescriptions in different settings provides an insight into the pattern of drug use, identifies drug-related problems and may be used to compare recommended guidelines with actual practice. This effort led to the evaluation of the drug prescribing pattern of antipsychotics in patients attending the psychiatric clinic at a government hospital. The data from 371 antipsychotic medication prescriptions that included 200 prescriptions for schizophrenia were collected during one month (1rst-31rst August 2008) at the outpatient pharmacy department. The mean age of patients was 35.0 years (SD = 1.131), with a male to female ratio of 2:1. The most widely used oral antipsychotic was haloperidol (16.3%) while the most common depot preparation prescribed was zuclopenthixol decanoate (8.8%). The daily dose of the average antipsychotic prescribed in this clinic was 342.06 mg equivalent of chlorpromazine. There was no relation between the doses received and ethnicity of the patient (Malay, Chinese or Indian). However, there was a significant relationship between the prescribed dose and patient age (P < 0.042). Nearly 32% of the schizophrenia patients were prescribed with atypical antipsychotics such as olanzapine (10.8%), risperidone (10.0%), quetiapine (7.6%) and clozapine (3.2%). Monotherapy was given to 73.0% of the schizophrenia patients. The majority of patients also received antidepressants. To conclude, this study gave evidence that physicians had a strong preference for monotherapy with conventional antipsychotic drugs while the use of atypical drugs was less prevalent.